2009
DOI: 10.1007/s10440-009-9464-y
|View full text |Cite
|
Sign up to set email alerts
|

Realization Theory for Rational Systems: Minimal Rational Realizations

Abstract: The study of realizations of response maps is a topic of control and system theory. Realization theory is used in system identification and control synthesis.A minimal rational realization of a given response map p is a rational realization of p such that the dimension of its state space equals the transcendence degree of the observation field of p. We relate minimality of rational realizations with their rational observability, algebraic controllability and canonicity. We show that the existence of a minimal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Moreover, it shows that if we consider as a field F from Proposition 5.14 the observation field of a response map to be realized, then the algorithm for constructing a rational realization from Proposition 5.14 gives as a result a rationally observable rational realization. Additional results which we got by studying minimal rational realization can be found in [15]. For some remarks on algebraic reachability of rational systems, see [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it shows that if we consider as a field F from Proposition 5.14 the observation field of a response map to be realized, then the algorithm for constructing a rational realization from Proposition 5.14 gives as a result a rationally observable rational realization. Additional results which we got by studying minimal rational realization can be found in [15]. For some remarks on algebraic reachability of rational systems, see [14].…”
Section: Discussionmentioning
confidence: 99%
“…. , α k ), α j ∈ U, k ∈ N, we get that ϕ = in [15]. They can be implemented by using already existing computer algebra packages.…”
Section: Canonical Rational Realizationsmentioning
confidence: 99%
“…These assumptions make it possible to study structural and global identifiability of parametrizations of parametrized polynomial and parametrized rational systems by means of realization theory developed in [5] for polynomial and in [26,25] for rational systems.…”
Section: Structural and Global Identifiabilitymentioning
confidence: 99%
“…We refer to the results of realization theory for rational systems in [26,25]. The main result which is applied to obtain this characterization is the following: This theorem corresponds to Theorem 4.2 in polynomial case.…”
Section: Structural Identifiability Of Rational Systemsmentioning
confidence: 99%
“…Further, Bartosiewicz (1987) established that a smooth system may be immersed into a rational system if the observation field is a finitely generated extension of R, and stated that rational systems could be simpler and more powerful than smooth systems. In addition, the existence of rational realizations of response maps was investigated in Němcová & van Schuppen (2009, 2010. It was shown that if a response map is realized by a rational system, then there also exists a minimal rational realization of the map (Němcová & van Schuppen, 2010).…”
Section: Introductionmentioning
confidence: 99%